The Supernatural World in a Community - Casaverde Rojas, Juvenal (1970)
In order to apply questionnaires and carry out research for the Program for Changes in Peruvian Peoples, they have remained in the Community of Kuyo Grande, under the coordination of Dr. Oscar Nuñez del Prado and the Supervision of Dr. Demetrio Roca, in September 1964, February and March 1965 and February and March 1966.